RESEARCH ADVANCES IN IMMUNE CHECKPOINT INHIBITORS IN TREATMENT OF HEAD AND NECK SQUAMOUS CELL CARCINOMA - LIU Hongbo, LU Jingyu, LU Haijun (精准医学杂志, 2023)
Head and neck squamous cell carcinoma (HNSCC) is a solid tumor with high morbidity. In recent years, traditional treatment methods, such as surgery, chemotherapy, and radiotherapy, are going through a bottleneck period, and therefore, new treatment methods are urgently needed to improve the prognosis of patients. Immunotherapy is an emerging treatment method for tumor in recent years, and immune checkpoint inhibitors (ICIs) have been widely used in the clinical treatment of HNSCC and other tumors with a marked clinical effect. This article summarizes the research advances in ICIs in the treatment of HNSCC and the effect of ICIs combined with radiotherapy and/or chemotherapy and elaborates on the adverse reactions of ICI the-rapy, in order to find the best paradigm of immunotherapy for HNSCC patients.